Studying neurotrophin antiviral effect on rabies-infected dorsal root ganglia cultures (2005)
Neurotrophin (NT)-induced modulation of rabies virus adsorption, transcription, and replication were analyzed in adult mouse dorsal root ganglia cultures. Different types of nerve growth factor and NT-3 treatment were tested before infection (pretreatment), during infection (transtreatment) and after withdrawing the viral inoculum (post-treatment). NT pretreatment for 4 days prior to infection produced a significant increase in the quantity of virus adsorbed into cultures and a concomitant increase in genomic viral RNA as measured by real time polymerase chain reaction (PCR). NT pretreatment triggered increased expression of two rabies virus receptors (NCAM and p75NTR); however, no increase in rabies virus transcription and expression could be observed. By contrast, NT treatment during and after infection (trans- and post-treatment) induced a strong decrease in the quantity of viral nucleoprotein genomic and messenger nucleoprotein RNAs. These findings suggested that NT had an intrinsic inhibitory effect on rabies virus infection, which was not counterbalanced by NTs’ rabies virus receptor—enhancing property and viral uptake. Adult mouse dorsal root ganglion cultures can be regarded as being a useful model for detecting therapeutic targets and evaluating experimental antiviral drugs.